Answer:
a(n) = -3 - 2(n-1)
Step-by-step explanation:
The most general formula for the nth term of an arithmetic sequence (such as this sequence is) is
a(n) = a(1) + c(n-1), where c is the common difference.
Here a(1) = -3 and c = -2.
Thus,
a(n) = -3 - 2(n-1).
Answer:
B
Step-by-step explanation:
Answer:
£159.82
Step-by-step explanation:
Decrease of 39% of £262
39/100 × £262
0.39×262
102.18
So the decrease will be
262-102.18
159.82
So the final answer is £159.82
Answer2 i would say bc it has the lest so it is ez to react
Step-by-step explanation:
Hey there!!
Scientific notation of 0.000000001 :
0.1 ⁻⁷
Hope it helps!